Old Ben Franklin's Philadelphia - Montgomery, Elizabeth Rider; Vestal, Herman B. (Champaign, Illinois : Garrard Publ. Co., 1967)
Descriptions of life in Philadelphia in 1787, the time of the Constitutional Convention covering customs, travel, dress, market, and fire fighting.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Philadelphia (Pa.) -- Social life and customs -- Juvenile literature